Impact of Blood Infections on Inflammatory Markers and Liver Function in Neonates with Pathological Jaundice in Erbil City: A Comprehensive Study - Hilal, Duaa Jammel; Rubaie, Ghadir M. N. Al; Sahar A. Ahmed; Asmaa Wajeh Jumaa (Journal of Science in Medicine and Life, 2025)
Neonatal pathological jaundice is a significant health concern, often complicated by blood infections which can alter physiological responses and exacerbate conditions. Understanding the impact of such infections on blood parameters and liver enzymes in newborns can aid in better diagnosis and management strategies. This study included 125 newborns treated at the Department of Obstetrics and Gynecology - Neonatal Intensive Care Unit at Erbil Hospital from January 2022 to June 2023. Participants were divided into two groups: 75 neonates with jaundice and confirmed bacterial blood inflammation and 50 neonates with jaundice but no bacterial infection. A control group of healthy infants was also included. Blood markers such as WBC, hs-CRP, PCT, and TRF, along with liver enzymes AST, GGT, and ALP, were measured using standardized laboratory procedures. Significant differences in blood markers were observed between the groups. Infants with jaundice and blood inflammation displayed elevated levels of WBC, hs-CRP, and PCT, indicating a strong inflammatory response (P < 0.05). TRF levels were notably lower in neonates with bacterial infections compared to those without, suggesting alterations in iron metabolism due to inflammation (P < 0.01). Liver enzyme analysis revealed higher AST, ALP, and GGT levels in jaundiced infants, which were more pronounced in those with concurrent blood infections, pointing towards potential liver involvement. The study highlights the clear impact of blood infection on both inflammatory markers and liver function in neonates with pathological jaundice. These findings suggest that close monitoring is critical for effective management of infants with jaundice. Future research should continue to explore the mechanisms driving these changes to enhance treatment protocols and outcomes in this vulnerable population.